EVALUATION OF THE DEGREE OF ACCUMULATION AND LOCAL IRRITANT ACTION OF THE DRUGS ESSIN/HP-BETTA-CD AND TAUCIN UNDER EXPERIMENTAL CONDITIONS - Z.Kh. Amonova; Sh.T. Makhmaraimov; M.Zh. Allaeva; D.D. Achilov (Central Asian Journal of Medicine, 2025)
The aim of the study was to investigate the degree of accumulation, local irritant effect of the preparations Essin/HP-betta-CD and Tautsin on laboratory animals: mice, rabbits. The degree of accumulation of Essin/HP-betta-CD was determined by administering the preparation to experimental mice. On the 8th day of the experiment, all mice showed signs of slowing down of movements, they became inactive for a short period of time and returned to normal after 60 minutes. The local irritant effect of the preparation Essin/HP-betta-CD was studied on laboratory rabbits. An hour after instillation of the preparation into the conjunctiva of the eyelids of rabbits, 75% of the experimental animals showed short-term serous discharge. When observing for 72 hours, no changes were found in the sclera and cornea of the eyes of rabbits, and the reaction and diameter of the pupil to light did not change. The local irritant effect of Taucine was tested on the eyes of rabbits, i.e. the drug was assessed by its ability to irritate the mucous membrane of the eye. For this purpose, 0.1 ml of a 1% solution of Taucine was instilled into the right eye of rabbits weighing 2.2–2.5 kg. 0.1 ml of distilled water was instilled into the left eye and used as a control. Both eyes of the animal were examined 1, 24, and 72 hours after the administration of the drug. The condition of the iris of the conjunctiva was assessed by the appearance of the mucous membrane, the structure of the blood vessels, and the presence or absence of tears.